2020 International Conference on ICT for Smart Society (ICISS) 2020
DOI: 10.1109/iciss50791.2020.9307553
|View full text |Cite
|
Sign up to set email alerts
|

Developing the government COVID-19 website: Lessons Learned from Jakarta

Abstract: Almost all countries obtain significant and multidimensional challenges of COVID-19. Various countries possess varied responses and policies regarding COVID-19. Since the Indonesian government affirmed COVID-19 a national emergency on March 2, 2020, it is necessary to have official information that can be accessed by the public, which at that time did not yet have the Central Government Website. Moreover, the importance of the availability of public information/data contained in official online pages can be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…An analysis from secondary sources has shown that smart city digital applications help facilitate social life and essential public service in the urban setting ( Rachmawati, Sari, et al, 2021 ). Other studies focus on a case study reporting specific ICT applications that support government business processes and public service deliveries during the pandemic ( Eryando et al, 2020 ; Gultom et al, 2020 ; Levyta et al, 2022 ).…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…An analysis from secondary sources has shown that smart city digital applications help facilitate social life and essential public service in the urban setting ( Rachmawati, Sari, et al, 2021 ). Other studies focus on a case study reporting specific ICT applications that support government business processes and public service deliveries during the pandemic ( Eryando et al, 2020 ; Gultom et al, 2020 ; Levyta et al, 2022 ).…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…Third, because of the community's growing apathy [4]. A critical requirement is the successful dissemination of information from stakeholders to the community and vice versa [5].…”
Section: Introductionmentioning
confidence: 99%